The minor prophets - Feinberg, Charles Lee (Chicago, IL Moody, 1976)
Includes bibliographical references and indexes.
Brethren writer. Originally published in 5 volumes in the series " The major messages of the minor prophets" c.1948-c.1952.
Keywords: Bible. O.T. Minor prophets -- commentaries